IDENTIFICATION OF THE THE INCOMING AIR FLOW INFLUENCE ON THE HEAT DISSIPATION OF DISK BRAKES (Transport systems and technologies, 2018)
Highlights the analysis of the factors of convective heat transfer in the brake disk during braking. The technique of calculating a speed of movement of air on the surfaceof the brake disc by the movement of the air flow. We study the dependence of the relative velocity of air on the surface of the brake disc from the speed of a railway vehicle. Determined the heat transfer coefficient by convection, which depends on the state of the gas flow, its physical properties, temperature and geometry of the bounding surfaces.During braking the speed of air flow high, and convective heat transfer affects the temperature of the brake disc. Thus, the heat transfer coefficient by convection of the brake disc becomes one of the key parameters of modeling thermal capacity of the railway brake disc. The air velocity at one point on the surface of the brake disc depends on the speed of the train and the linear velocity of disc rotation. In the actual process of braking at high speed trains the angles between the train speed and the linear speed of each point change. Consequently, there is a need for equivalent coefficient of air velocity. The resulting ratio is equivalent to the velocity of the air expresses the dependence of the relative velocity of air on the surface of the brake disc from the speed of a railway vehicle. The obtained results allow to consider the parameters of movement of air flow when calculating the heat transfer coefficient by convection.
Keywords: railway transport, convective heat dissipation, brake system, airflow.